Dampak Sistem Penanganan Elektronik Emergency di Instalasi Gawat Darurat: Scoping Review - Nofita Dewi Kok Mesa; Dedy Arisjulyanto; Frans Manangsang; Evangelin Watunglawar; Fajar Bakti Kurniawan (Yayasan Literasi Sains Indonesia, 2025)
The density of the number of various cases of critical and emergency patients makes it a major problem in the emergency room, making the workload of officers increase. The emergency electronic system is also a pro/con for medical personnel in the emergency room. Some have negative and positive impacts. Its positive benefits include helping to facilitate complete patient records, improving reporting, reducing data entry errors. The purpose of this literature review was to see the impact of Emergency Electronic Handling Systems in Emergency Installations. The method used in this study is Scoping Review and is carried out systematically based on PRISMA. The determination of article search keywords using the keywords used is